A Review of the Impact of Climatic Factors on the Performance of Oxidation Pond (OP) and Its Linkage to the Circular Economy - Kundan Samal; Satya Ranjan Samal; Soumyaranjan Senapati; Alok Kumar Panda; Narala Gangadhara Reddy (Air, Soil and Water Research)
The increasing focus on sustainable and environmentally friendly solutions has led to the exploration of various wastewater treatment technologies. Among these, oxidation ponds (OPs) have gained significant attention due to their low operational costs and minimal energy requirements. However, the performance of OPs can be shaped by multiple climatic parameters, incorporating sunlight, temperature, wind, precipitation, evaporation and seasonal variation. The circular economy concept emphasizes the recovery and reuse of resources, promoting sustainability and reducing waste generation. OPs offer opportunities for resource recovery, including the generation of algae biomass, that could be utilized as a feedstock for biofuels, fertilizers, or animal feed. The climatic factors affecting OP performance can also impact the productivity and composition of the algae, thereby influencing the potential applications of these resources within the circular economy framework. This review examines the existing literature on the impact of sunlight, temperature, wind, precipitation, evaporation and seasonal variation on OP performance, highlighting their effects on treatment efficiency, microbial dynamics, and resource recovery potential. The findings underscore the importance of considering climatic factors in the design and operation of OPs to optimize their performance and maximize their contribution to the circular economy. Future research directions are suggested to further explore the synergistic relationship between climatic factors, OP performance, and circular economy linkages, with the aim of developing sustainable and resilient wastewater treatment systems.